Complications associated with bone marrow sampling in dogs and cats. (4th December 2020) - Woods, G. A.; Simpson, M.; Boag, A.; Paris, J.; Piccinelli, C.; Breheny, C.
Abstract : Objectives: To evaluate the prevalence of complications during bone marrow sampling and associated patient and procedural factors in dogs and cats. Materials and Methods: Retrospective cohort study, records were evaluated to identify dogs and cats that had bone marrow sampling between 2012 and 2019. Data including signalment, the presence of specific clinicopathological findings, anatomical site of bone marrow sampling, number of attempts, diagnostic quality of sampling, analgesia protocol and complications postprocedure were recorded. Results: A total of 131 dogs and 29 cats were included in the study. Complications were recorded in 22 of 160 (14%) of cases. Pain was the most common complication of bone marrow sampling in 20 of 22 (91%) of cases with bruising reported in the remaining patients. A local anaesthetic block was used in 98 of 160 (61%) of patients. Clinical Significance: Excluding pain, complications associated with bone marrow sampling were rare and no clear association were detected between patient or procedural variables. Haemorrhage and infection are rare complications in dogs and cats when thrombocytopenia and neutropenia are present. Peri‐procedure analgesia is strongly recommended to minimise complications.